Desenvolvimento de imunossensores piezelétrico e eletroquímico para detecção de amostras de interesse agronômico e de saúde - Afonso, André Santiago (2012)
This work shows development of immunosensors for agronomic interest and public heath. The first was a piezoeletric immunosensor to detect a cysteine peptidase, a potencial biomarker for Xanthomonas citri subsp. citri that cause a citrus Canker. Another was electrochemical immunosensor based on gold nanoparticles as a label and magnetic beads as capture phase of Salmonella enterica subsp. enterica sorovar Typhimurium LT2 (S). The piezoelectric immunoassay was based on immobilization of polyclonal antibody against CPXaC (anti-CPXaC), produced in rabbit, onto three different monolayers that modified gold quartz crystal, which were evaluated by monitoring frequency and energy dissipation in real time when 64.5×10-8 mol L-1 of CPXaC was added. The better relation between analytical response and energy dissipation was obtained with immobilization onto 11- mercaptoundecanoic acid which presented a detection limit of 13.0 nmol L-1 as well as good values for the kinetic and equilibrium binding constant. The immunosensor showed good specificity with no response for different proteins include another cysteine peptidase that is used as a target for detects Xylella fastidiosa bacterium responsible for other important disease in citrus. For detection of Salmonella using a magneto-immunoassay and gold nanoparticles (AuNPs) as label was developed based on the use of a screen-printed carbon electrode (SPCE) that incorporates a permanent magnet underneath. Salmonella spiked in milk samples (i.e. skimmed milk) have been tested by using anti-Salmonella magnetic beads (MBs-SAb) as capture phase and sandwiching afterwards with AuNPs modified antibodies (SAb-AuNPs). AuNPs detection using differential pulse voltammetry (DPV) following a previous established procedure is performed. And a detection limit of 143 CFU mL-1 and a linear range of from 103 to 106 CFU mL-1 of Salmonella, with a coefficient of variation of about 2.4%, was obtained. Recoveries of the sensor by spiking skimmed milk with different quantities of Salmonella of about 83 and 94 % for xviii 1.5 x 103 and 1.5 x 105 CFU mL-1 were obtained, respectively. This work demonstrated the possibility to detect CPXaC with a piezoelectric immunosensor as well as electrochemical immunosensor to detect Salmonella spiked in milk samples.